2011
DOI: 10.1021/ol200572p
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photosensitized Singlet Oxygen Generation Efficiency of Novel Aza-BODIPY Dyes

Abstract: The statement "However, the triplet quantum yields and the singlet oxygen generation efficiency of those dyes were found to be relatively low" was incorrect. This sentence should be corrected as "The triplet quantum yields and the singlet oxygen generation efficiency of those dyes were found to be good to quantitative depending on the substitution".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Tetraiodinated BODIPY 28 showed about 87% of singlet oxygen quantum yield compared to Rose Bengal (71%). The introduction of iodine atoms in the pyrrole ring of aza-BODIPY derivatives also improved the intersystem crossing efficiency, which was prepared by reacting 29 (long wavelength) with 4.5 equiv of N-iodosuccinimide in a 3 : 1 mixture of chloroform/ acetic acid at 25 uC for 10 h. 89,90 …”
Section: E Structural Modification Of Bodipy-based Photosensitizers mentioning
confidence: 99%
“…Tetraiodinated BODIPY 28 showed about 87% of singlet oxygen quantum yield compared to Rose Bengal (71%). The introduction of iodine atoms in the pyrrole ring of aza-BODIPY derivatives also improved the intersystem crossing efficiency, which was prepared by reacting 29 (long wavelength) with 4.5 equiv of N-iodosuccinimide in a 3 : 1 mixture of chloroform/ acetic acid at 25 uC for 10 h. 89,90 …”
Section: E Structural Modification Of Bodipy-based Photosensitizers mentioning
confidence: 99%
“…In the case of oxygen molecules, an additional mechanism related to Förster resonant energy transfer (FRET) can also play an important role remarkably influencing PL behaviour of silicon nanostructures. It has been shown that effective generation of singlet oxygen can be provoked by external sensitizers like dye molecules [Awuah 2011, Adarsh 2010Shi 2006;DeRosa 2002]. Moreover, silicon nanostructures can also play role of effective photosensitizers of singlet oxygen generation.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…S8, ESI †) and F is the absorption correction factor, which is given by F = 1-10 −OD (OD at the irradiation wavelength). 41 Determination of the minimum inhibitory concentration (MIC) 42 The…”
Section: Measurement Of Singlet Oxygen Production Efficiencymentioning
confidence: 99%